Estudo comparativo de restos fósseis e recentes de Amphisbaenia: abordagens filogenéticas, paleoecológicas, paleobiogeográficas - Benites, João Paulo de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Amphisbaenia is an important group of reptilian amniotes, provided with cylindrical and elongated body, usually limbless, with the exception of the Family Bipedidae, which presents limbs. This anatomy facilitates fossorial life. They are allocated to Squamata, by having hemipenis, tooth to break the egg, cross cloacal vent and integument covered with scales. Resembling lacertilians and snakes, their phylogenetic position has been widely discussed and their ancestry is still controversial. They are limited to subtropical and tropical regions, providing important paleoecological and paleobiogeographical informations to the group. They cave deep tunnels, compacting soil, which implies major morphological changes, such as robust skull bones, with rigid plates, and strong osteological connections in the frontal region, with superimposed bones, giving them greater resistance to impacts during excavation. Their anatomy is quite convergent with Mesozoic lacertiform fossils, showing a probable common ancestor with these diapsids. A specimen of VIII Cryptolacerta, from Germany, shares features with Amphisbaenia. However its phylogeny is still uncertain. But Sineoamphisbaena may indicate convergent features between Laurasian lizards, possibly with those originated Amphisbaenia. The fossil records are geographically restricted, predominantly from USA, in relatively small quantity. Most are related to the Family Rhineuridae, which could be considered primitive. However the Family Bipedidae, a recent group, is classified also as primitive, due to the presence of shoulder girdle and forelimbs. But Bipedidae does not present fossils, because until now there are not fossilized remains assigned to them. Morphological convergence occurs in Rhineuridae, detailed in phylogenetic analyses, placing it as a apomorphic group. Anyway it is clear that the origin of Amphisbaenia remains obscure. There are not well preserved fossil materials before beginning of Eocene

Amphisbaenia é um importante grupo de amniotas reptilianos, providos de corpo cilíndrico e alongado, usualmente desprovidos de membros, com a exceção da Família Bipedidae, que apresentam os anteriores desenvolvidos. Esta anatomia facilita a vida fossorial. São alocados aos Squamata, por possuírem hemipênis, dente para romper e sair do ovo, cloaca transversal e tegumento coberto de escamas. Por assemelharem-se a lacertílios e ofídios, seu posicionamento filogenético tem sido amplamente discutido e sua ancestralidade é ainda controversa. São limitados às regiões subtropicais e tropicais, constituindo importante informação para abordagens paleoecológicas e paleobiogeográficas. Confeccionam profundos túneis compactando o solo, o que implica em grandes modificações morfológicas, tais como crânio robusto, formado por placas ósseas rígidas, e ligações interdigitais na região frontal, podendo ser sobrepostas, o que lhes confere maior resistência contra impactos na escavação. Sua anatomia é bastante convergente com aquela dos fósseis de lacertiformes mesozóicos, demonstrando um provável ancestral em comum com estes diápsidos. Um espécimen de Cryptolacerta, oriundo da Alemanha, compartilha características com Amphisbaenia. Entretanto sua filogenia ainda é incerta. De todo modo, junto com Sineoamphisbaena, pode indicar características convergentes entre lagartos laurasianos, possivelmente com aqueles que originaram Amphisbaenia. Os fósseis de anfisbênios são geograficamente restritos, predominantemente encontrados nos Estados Unidos, em quantidade relativamente escassa. A maior parte está relacionada à Família Rhineuridae, que poderia ser considerada primitiva. No entanto Bipedidae, um grupo recente, também é considerado como primitivo, devido à presença de cintura escapular e membros anteriores. Entretanto não há registros fósseis seguros, pois até então não foram encontrados restos fossilizados..
Keywords: Vertebrates, Fossil; Vertebrado fossil; Filogenia; Paleoecologia; Paleobiogeografia